Features of pancreatic parenchyma fibrosis in the comorbid course of chronic pancreatitis and chronic obstructive pulmonary disease - I.V. Dudka; O.S. Khukhlina; T.V. Dudka; O.Y. Hryniuk; V.O. Pavliuk (Medičnì Perspektivi)
Under the conditions of chronic obstructive pulmonary disease (COPD), chronic pancreatitis (CP) progresses with the development of exocrine pancreatic insufficiency (EPI), which occurs when the active area of the acinar epithelium decreases as a result of the inflammatory process and fibrosis of the organ. The objective of the study was to study the peculiarities of the processes of the pancreas tissue fibrosis in patients with chronic pancreatitis in case of comorbidity with chronic obstructive pulmonary disease. A prospective cohort study was conducted with the analysis of inpatients’ medical records of 305 patients. The first group of patients consisted of 96 people with an isolated course of CP, the second group consisted of 116 patients with CP with comorbid COPD, the third group consisted of 93 patients with isolated COPD. The comparison group consisted of 30 practically healthy persons. The study also used data from a clinical blood analysis, a biochemical study of the content of markers of the syndrome of deviation of the pancreas enzymes in the blood, the content of elastase-1 in feces, ultrasonographic examination of abdominal organs, changes in the carbohydrate-protein components of the extracellular matrix, the state of collagenolytic activity of the blood plasma. In patients with CP in the exacerbation phase without comorbid pathology, as well as with comorbid COPD and isolated COPD, a significant activation of fibrosing reactions was established: activation of collagen synthesis was registered as an indicator of an increase in the content of protein-bound oxyproline (PBOP) in the blood: in patients of the 1st group – 1.7 times, patients of the 2nd group – 2.1 times and 3rd group – 2.3 times (p<0.05). The specified direction of changes is confirmed by the indicator of the content of type IV collagen in the blood, which increased in comparison with the indicator in practically healthy persons, respectively, in patients of groups 1, 2, 3 – by 1.4 times, 2.4 and 2.5 times (p<0.05), i.e. maximally in patients with COPD and with comorbidity of CP with COPD. In patients with a comorbid course of CP and COPD, a correlational interdependence was established between the indicators of the state of the protein components of the connective tissue of the extracellular matrix of the pancreas (PBOP) and hyperamylasemia (r=0.32, p<0.05), the intensity of endotoxicosis (r=0, 37, p<0.05), the level of glycemia (r=0.45, p<0.05), and the inverse relationship between the content of elastase-1 in feces (r=-0.33, p<0.05 ), insulinemia (r=-0.46, p<0.05), which indicates the interdependence of these changes and their role in the pathogenesis of the progression of chronic pancreatitis. Correlation relationship between the parameter of ultrasonographic histography of the pancreas – L, which indicates the degree of the pancreas fibrosis, and the content of type IV collagen in the blood (r=0.54, p<0.05), the content of PBOP in the blood (r=0.46, p<0.05), hexosamines (r=0.38, p<0.05) points to the biochemical mechanisms of the pancreas fibrosis and opens up prospects for developing the ways of pathogenetic correction and prevention of CP progression in comorbidity with COPD.